The effects of resveratrol on tendon healing of diabetic rats - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2014)
Objective: The aim of this study was to determine the effects of resveratrol on the tendon healing process of streptozotocin-induced diabetic rats. Methods: The study included 16 male Sprague-Dawley rats. Streptozotocin was administered to induce diabetes and bilateral tenorrhaphy of the Achilles tendons was performed. Intraperitoneal resveratrol was injected in the experimental group (n=8) and saline in the control group (n=8) during the postoperative period. Rats were sacrificed at the 14th day. Right side tendons were evaluated biomechanically and left side tendons histologically. Results: Difference in mean tendon tensile strength was not statistically significant between groups (p>0.05). Histologic evaluations of the repair zones showed greater configuration of the newly synthesized collagen in the experimental group. The ratio of the newly synthesized collagen area to the healing region area was significantly higher in the experimental group then the control group (p<0.01). Conclusion: Resveratrol appears to have a positive impact on the process of tendon healing in diabetic conditions in the first 14 days.
Keywords: Diabetic; resveratrol; tendon healing; tensile strength; ACHILLES-TENDON; MODEL; TRANSLOCATION; GLUT-4; REPAIR